Analisis Penyebaran dan Komparasi Skenario Kebijakan Penanggulangan Covid-19 berbasis Sistem Dinamik - Adi Akhmadi Pamungkas; Hammam Riza; Arwanto; Sri Handoyo Mukti (APIC, 2020)
The emergence of a new variant of the coronavirus, SARS-Cov-2, which causes the Corona Virus Disease (Covid-19) outbreak has really changed the world. First reported in Wuhan City, Hubei Province, China at the end of 2019, this virus has spread throughout the world. Apart from hitting the world economy, the Covid-19 pandemic has also changed the way humans interact. All over the world, people have changed their habits of work, worship, and social activities. This was done to reduce the risk of transmission of the massive new coronavirus. But the next question arises: when will conditions improve? when will this Covid-19 outbreak subside? To answer this question, this study seeks to model the spread of the new Corona Virus with a Dynamic Systems approach. In the modelling carried out, there are seven scenarios that describe the policies undertaken to mitigate the spread of Covid-19 which include WFH policies, office vacations, social distancing, implementation of PSBB, to PSBB relaxation. The resulting model is then validated with data from the Covid-19 Handling Acceleration Task Force which is released every day. Of the seven modelled scenarios, the fastest pandemic relief time is predicted to occur on September 25, 2020, as indicated by scenario 0 with a prediction of a total of 530,655 positive cases. The longest pandemic relief time is predicted to occur on July 17, 2021, with a prediction of a total of 269,115 positive cases.